Preparation of lithium iron phosphate nanospheres
By adding surface active agents and doped metal ions during the preparation of lithium iron phosphate electrode materials to change the internal structure of the crystal, solve the restrictions of lithium iron phosphate electrode materials in terms of charging and discharge performance and cycle stability. Battery performance.
Patent Information
- Application Number
- CN202310925151.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-26
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2043-07-26
AI Technical Summary
The existing lithium iron phosphate electrode materials have limitations in charge and discharge performance and cycle stability, and it is difficult to meet the needs of efficient applications of lithium-ion batteries.
Add the surfactant during the process of preparing FEPO4, and change the internal structure of the crystal by doping sulfate sulfate and sulfate migration LI3PO4 to improve the charging and discharge performance of lithium iron phosphate.
Through the modification process, the power and other performance of lithium iron phosphate is significantly improved, and the vibration density and circulation performance of the material are enhanced.
Smart Images

Figure CN119370814A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the preparation of nanospheres, in particular to lithium iron phosphate nanospheres, and in particular to the preparation of lithium iron phosphate nanospheres. Background Art
[0002] In recent years, lithium-ion batteries, as a rechargeable energy storage system, have been considered to be a substitute for fossil fuels and alleviate the increasingly prominent environmental and energy problems due to their advantages such as no pollution, high energy density and good cycle stability. As an important part of lithium-ion batteries, the selection of electrode materials is very important, because good electrode materials have very broad prospects in improving battery performance. Therefore, in order to ensure the excellent performance of lithium-ion batteries, electrode materials with good performance should be selected.
[0003] Since 1997, the cathode material LiFePO4 (lithium iron phosphate) with advantages such as high theoretical capacity, good safety, long cycle life and low cost has attracted people's attention. It can be obtained from the charging and discharging process that the product of lithium iron phosphate after complete delithiation is the iron phosphate phase. Due to its advantages such as low cost and high chemical stability, FePO4 as a trivalent iron source is considered to be an ideal material for synthesizing lithium iron phosphate. The structure, morphology, particle size distribution, etc. of iron phosphate all affect the performance of lithium iron phosphate. By controlling the crystal size and morphology of the iron phosphate precursor, it can be used to achieve large-scale production of LiFePO4 with high tap density, high discharge rate and high capacity, overcoming the limitation of ionic conductivity of LiFePO4 to a certain extent, and then realizing various high-efficiency applications in the later stage. Therefore, as an important precursor of lithium iron phosphate, a cathode material of lithium-ion batteries, the preparation of a precursor iron phosphate with good morphology, particle size and other properties is the first step and the most critical step. Summary of the invention
[0004] In view of the above problems, the present invention adds a surfactant during the preparation of the FePO4 precursor, so that the iron phosphate is spherical, and uses cerium sulfate and europium sulfate to modify Li3PO4. The lithium iron phosphate generated by the reaction of the modified Li3PO4 and FePO4 can change the internal structure of the crystal and significantly improve the charge and discharge performance and other properties of the lithium iron phosphate. The preparation process of the present invention is simple and easy to operate. The charge and discharge performance of the lithium iron phosphate is further improved by the modified FePO4 precursor prepared by the present invention and the use of modified Li3PO4. The specific preparation steps are as follows:
[0005] S1. Preparation of FePO4 precursor: Dissolve (NH4)2Fe(SO4)2·6H2O and NH4H2PO4 in 500mL of deionized water at a molar ratio of 1:1. Slowly add the NH4H2PO4 solution to the (NH4)2Fe(SO4)2·6H2O solution using a peristaltic pump, stir at 10℃~20℃ to form a uniform colloidal solution, then drop 1mL~5mL of 30% H2O2 solution as an oxidant into the colloidal solution, stir the solution for another 1h~2h to form a light yellow FePO4·3H2O precipitate;
[0006] S2, collecting the precipitate in S1 by centrifugation, repeatedly washing with deionized water, and drying the final product in a drying oven at 60°C to 80°C for 10h to 12h, placing the FePO4·3H2O precursor in a muffle furnace at 675°C to 825°C for calcination to obtain an iron source;
[0007] S3. Add cerium sulfate and europium sulfate in a doping ratio of 1:1 to Li3PO4, stir evenly, transfer the mixed solution into a reactor, and react for 1h to 2h to obtain modified Li3PO4; there is a synergistic effect between cerium ions and europium ions, so that the nanospheres present a better spherical morphology. Particles with this morphology increase the contact area between the particles and the electrolyte, thereby greatly improving the electrical properties of the material.
[0008] S4, take the iron source obtained from S2 and the modified Li3PO4 obtained from S3 in a mass ratio of 1:1.5, dissolve them in deionized water, stir them evenly, then add the cationic surfactant octadecyl dimethyl benzyl ammonium chloride, the addition amount of octadecyl dimethyl benzyl ammonium chloride is 2.5% to 3.5% of the mass of the iron source, then put them into a reactor for hydrothermal reaction, the pH is 1.45, the reaction temperature is 100℃ to 120℃, the reaction time is 4h to 6h, collect the solid powder in the reactor, filter it and vacuum dry it at 50℃ to 80℃ for 2h to 3h; modify the FePO4 precursor with the cationic surfactant octadecyl dimethyl benzyl ammonium chloride, and the use of the cationic surfactant octadecyl dimethyl benzyl ammonium chloride with the function of dispersing particles can achieve effective control of particle size and morphology.
[0009] S5. Place the dried solid powder in S4 in a tube furnace, calcine at 525°C to 625°C for 10h to 16h under the protection of argon, and cool to room temperature to obtain LiFePO4 product.
[0010] Preferably, the materials used in step S1 are 0.02 mol of (NH4)2Fe(SO4)2·6H2O and NH4H2PO4.
[0011] Preferably, the product in step S2 is dried in a drying oven at 80° C. for 12 hours.
[0012] Preferably: in step S3, the mixed solution is transferred into a reactor to react for 1.5 hours.
[0013] Preferably, the amount of octadecyldimethylbenzylammonium chloride added in step S4 is 3.0% of the mass of the iron source.
[0014] Preferably, in step S5, calcination is performed in a tube furnace at 625° C. for 16 hours.
[0015] Preferably: the (NH4)2Fe(SO4)2·6H2O and NH4H2PO4 described in the present invention are purchased from Henan Seoul Environmental Protection Technology Co., Ltd.
[0016] Preferably: the cerium sulfate and europium sulfate described in the present invention are purchased from Hubei Baidu Chemical Co., Ltd.
[0017] Preferably: the octadecyl dimethyl benzyl ammonium chloride of the present invention is purchased from Hubei Chengfeng Chemical Co., Ltd.
[0018] The beneficial effects of the present invention are:
[0019] 1. The present invention relates to a lithium iron phosphate nanosphere, wherein a FePO4 precursor is modified by a cationic surfactant octadecyl dimethyl benzyl ammonium chloride, and the cationic surfactant octadecyl dimethyl benzyl ammonium chloride having the function of dispersing particles can effectively control the particle size and morphology. Therefore, a small amount of surfactant is added as a dispersant, and the agglomeration of particles can be avoided or reduced during the synthesis process of the iron phosphate particles, thereby obtaining a powder with good morphology and uniform particle size, so as to improve the tap density.
[0020] 2. The present invention uses modified Li3PO4. The reaction of the modified Li3PO4 and FePO4 can significantly improve the charge-discharge performance and other properties of lithium iron phosphate. Metal cerium ions and metal europium ions are usually embedded in the iron phosphate lattice, causing the atomic spacing and position in the crystal to change accordingly, causing the unit cell to shrink, changing the internal structure of the crystal, and thus affecting the external morphology of iron phosphate. Doping with metal ions can effectively increase the tap density of the material, thereby improving the volumetric capacity and cycle performance of lithium iron phosphate. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative labor.
[0022] Figure 1 This is a SEM image at a magnification of 10 μm of lithium iron phosphate without adding a surfactant according to the present invention.
[0023] Figure 2 This is a SEM image of lithium iron phosphate to which a cationic surfactant octadecyl dimethyl benzyl ammonium chloride is added at a magnification of 10 μm.
[0024] Figure 3 The figure shows the effect of adding different iron source masses of octadecyldimethylbenzylammonium chloride on the specific surface area of the nanospheres in Example 2 of the present invention and Comparative Examples 2 to 5.
[0025] Figure 4 This is a 5 μm magnification SEM image of the invention in which cerium sulfate and europium sulfate are added in a doping ratio of 1:1.
[0026] Figure 5 This is a SEM image with a magnification of 5 μm in which cerium sulfate is added to the present invention.
[0027] Figure 6 This is a SEM image of the invention with a magnification of 5 μm when europium sulfate is added. DETAILED DESCRIPTION
[0028] In order to make the technical problems, technical solutions and beneficial effects to be solved by the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the content of the present invention and are not used to limit the present invention.
[0029] Example 1
[0030] S1. Preparation of FePO4 precursor: (NH4)2Fe(SO4)2·6H2O and NH4H2PO4 (Henan Seoul Environmental Protection Technology Co., Ltd.) with a molar ratio of 1:1 were dissolved in 500 mL of deionized water, and the NH4H2PO4 solution was slowly added to the (NH4)2Fe(SO4)2·6H2O solution using a peristaltic pump. The solution was stirred at 10°C to form a uniform colloidal solution. Then, 3 mL of 30% H2O2 solution was added dropwise as an oxidant to the colloidal solution. The solution was stirred for another 2 h to form a light yellow FePO4·3H2O precipitate.
[0031] S2, collecting the precipitate in S1 by centrifugation, repeatedly washing with deionized water, and drying the final product in a drying oven at 80°C for 12 h, and calcining the FePO4·3H2O precursor in a muffle furnace at 725°C;
[0032] S3, adding cerium sulfate and europium sulfate (Hubei Baidu Chemical Co., Ltd.) in a doping ratio of 1:1 to Li3PO4, stirring evenly, transferring the mixed solution into a reactor, reacting for 2 hours, and obtaining modified Li3PO4;
[0033] S4, take the iron source obtained from S2 and the modified Li3PO4 obtained from S3 in a mass ratio of 1:1.5, dissolve them in deionized water, stir them evenly, then add the cationic surfactant octadecyl dimethyl benzyl ammonium chloride (Hubei Chengfeng Chemical Co., Ltd.), the addition amount of octadecyl dimethyl benzyl ammonium chloride is 3.0% of the mass of the iron source, then put them into a reactor for hydrothermal reaction, pH is 1.45, reaction temperature is 120°C, reaction time is 6h, collect the solid powder in the reactor, filter it and vacuum dry it at 80°C for 3h;
[0034] S5. The dried solid powder in S4 is placed in a tube furnace, calcined at 625° C. for 16 h under the protection of argon, and cooled to room temperature to obtain LiFePO4 product.
[0035] In Comparative Example 1, no cationic surfactant is added in step S3, and the rest is the same as Example 1.
[0036] Figure 1 It is lithium iron phosphate without adding surfactant, its particle dispersibility is poor, the morphology is flaky particles, and the particle distribution is uneven. Figure 2 It is lithium iron phosphate to which the cationic surfactant octadecyl dimethyl benzyl ammonium chloride is added, and it presents a quasi-spherical morphology. The addition of surfactant has a great influence on the particle size and morphology of lithium iron phosphate. It can reduce the agglomeration phenomenon between particles and control the growth of iron phosphate particles. Spherical lithium iron phosphate can improve the fluidity of the material and the compaction density of the pole piece, thereby improving the volume energy density of lithium iron phosphate. Spherical lithium iron phosphate is easier to form a uniform carbon coating, which helps to improve the conductivity of the positive electrode material. The contact between spherical lithium iron phosphates is point contact, so less adhesive is needed to achieve the fixing effect. It can be concluded that lithium iron phosphate to which the cationic surfactant octadecyl dimethyl benzyl ammonium chloride is added will obtain a powder with better morphology and uniform particle size to improve the tap density.
[0037] Example 2
[0038] S1. Preparation of FePO4 precursor: (NH4)2Fe(SO4)2·6H2O and NH4H2PO4 (Henan Seoul Environmental Protection Technology Co., Ltd.) with a molar ratio of 1:1 were dissolved in 500 mL of deionized water, and the NH4H2PO4 solution was slowly added to the (NH4)2Fe(SO4)2·6H2O solution using a peristaltic pump. The solution was stirred at 10°C to form a uniform colloidal solution. Then, 3 mL of 30% H2O2 solution was added dropwise to the colloidal solution as an oxidant. The solution was stirred for another 2 h to form a light yellow FePO4·3H2O precipitate.
[0039] S2, collecting the precipitate in S1 by centrifugation, repeatedly washing with deionized water, and drying the final product in a drying oven at 80°C for 12 h, and calcining the FePO4·3H2O precursor in a muffle furnace at 725°C;
[0040] S3, adding cerium sulfate and europium sulfate (Hubei Baidu Chemical Co., Ltd.) in a doping ratio of 1:1 to Li3PO4, stirring evenly, transferring the mixed solution into a reactor, reacting for 2 hours, and obtaining modified Li3PO4;
[0041] S4, take the iron source obtained from S2 and the modified Li3PO4 obtained from S3 in a mass ratio of 1:1.5, dissolve them in deionized water, stir them evenly, then add the cationic surfactant octadecyl dimethyl benzyl ammonium chloride (Hubei Chengfeng Chemical Co., Ltd.), the addition amount of octadecyl dimethyl benzyl ammonium chloride is 3.0% of the mass of the iron source, then put them into a reactor for hydrothermal reaction, pH is 1.45, reaction temperature is 120°C, reaction time is 6h, collect the solid powder in the reactor, filter it and vacuum dry it at 80°C for 3h;
[0042] S5. The dried solid powder in S4 is placed in a tube furnace, calcined at 625° C. for 16 h under the protection of argon, and cooled to room temperature to obtain LiFePO4 product.
[0043] Comparative Example 2 is the same as Example 2 except that 0.5% of the mass of the iron source is added to octadecyldimethylbenzylammonium chloride in step S3.
[0044] Comparative Example 3 is the same as Example 2 except that 1.0% of the mass of the iron source is added to octadecyldimethylbenzylammonium chloride in step S3.
[0045] Comparative Example 4 is the same as Example 2 except that 2.0% of the mass of the iron source is added in step S3.
[0046] Comparative Example 5 is the same as Example 2 except that 4.0% of the mass of the iron source is added in step S3.
[0047] Figure 3 The effect of the amount of octadecyl dimethyl benzyl ammonium chloride additive on the specific surface area. The effect of the amount of octadecyl dimethyl benzyl ammonium chloride on the specific surface area first increases and then decreases, and when the amount is 3.0% of the iron source mass fraction, it reaches a maximum value of 84.35m 2 / g. The use of cationic surfactant octadecyl dimethyl benzyl ammonium chloride with the function of dispersing particles can effectively control the particle size and morphology. Adding 3.0% of the iron source mass fraction of octadecyl dimethyl benzyl ammonium chloride will increase the contact area between the lithium iron phosphate material and the electrolyte, shortening the Li + The migration path in the LiFePO4 primary particles is beneficial to improving the specific capacity of LiFePO4.
[0048] Example 3
[0049] S1. Preparation of FePO4 precursor: (NH4)2Fe(SO4)2·6H2O and NH4H2PO4 (Henan Seoul Environmental Protection Technology Co., Ltd.) with a molar ratio of 1:1 were dissolved in 500 mL of deionized water, and the NH4H2PO4 solution was slowly added to the (NH4)2Fe(SO4)2·6H2O solution using a peristaltic pump. The solution was stirred at 10°C to form a uniform colloidal solution. Then, 3 mL of 30% H2O2 solution was added dropwise to the colloidal solution as an oxidant. The solution was stirred for another 2 h to form a light yellow FePO4·3H2O precipitate.
[0050] S2, collecting the precipitate in S1 by centrifugation, repeatedly washing with deionized water, and drying the final product in a drying oven at 80°C for 12 h, and calcining the FePO4·3H2O precursor in a muffle furnace at 725°C;
[0051] S3, adding cerium sulfate and europium sulfate (Hubei Baidu Chemical Co., Ltd.) in a doping ratio of 1:1 to Li3PO4, stirring evenly, transferring the mixed solution into a reactor, reacting for 2 hours, and obtaining modified Li3PO4;
[0052] S4, take the iron source obtained from S2 and the modified Li3PO4 obtained from S3 in a mass ratio of 1:1.5, dissolve them in deionized water, stir them evenly, then add the cationic surfactant octadecyl dimethyl benzyl ammonium chloride (Hubei Chengfeng Chemical Co., Ltd.), the addition amount of octadecyl dimethyl benzyl ammonium chloride is 3.0% of the mass of the iron source, then put them into a reactor for hydrothermal reaction, pH is 1.45, reaction temperature is 120°C, reaction time is 6h, collect the solid powder in the reactor, filter it and vacuum dry it at 80°C for 3h;
[0053] S5. The dried solid powder in S4 is placed in a tube furnace, calcined at 625° C. for 16 h under the protection of argon, and cooled to room temperature to obtain LiFePO4 product.
[0054] Comparative Example 6 is the same as Example 3 except that cerium sulfate is added in step S4.
[0055] Comparative Example 7 is the same as Example 3 except that europium sulfate is added in step S4.
[0056] Figure 4 This is a SEM image of lithium iron phosphate nanospheres doped with cerium sulfate and europium sulfate in a ratio of 1:1. Figure 4 Not only is the sphericity the best, but the surface is also the smoothest, and the primary particles are between 100 and 200 nm. The reason for the small size of the primary particles of lithium iron phosphate can be attributed to the small primary particles of ferrous phosphate itself. During the sintering process, lithium iron phosphate crystals are transformed from ferrous phosphate crystals, so the particle size of ferrous phosphate itself will have a direct impact on the particle size of lithium iron phosphate. It will accelerate the conduction of electrons and ions between particles. Figure 5 This is a SEM image of lithium iron phosphate nanospheres doped with cerium sulfate. It can be seen from the image that the surface of the nanospheres is not smooth. Figure 6 This is a SEM image of lithium iron phosphate nanospheres doped with europium sulfate. The surface of the nanospheres is Figure 5 Slightly smooth, but not as smooth as Figure 4 The nanospheres are smooth. The reason may be the synergistic effect between cerium ions and europium ions, which makes the lithium iron phosphate nanospheres present a better spherical morphology. Particles with this morphology increase the contact area between the particles and the electrolyte, thereby greatly improving the electrical properties of the material.
Claims
1. A preparation method of lithium iron phosphate nanospheres, characterized in that: The specific steps are as follows: S1. Preparation of FePO4 precursor: (NH4)2Fe(SO4)2·6H2O and NH4H2PO4 with a molar ratio of 1:1 were dissolved in 500 mL of deionized water, and the NH4H2PO4 solution was slowly added to the (NH4)2Fe(SO4)2·6H2O solution using a peristaltic pump. The mixture was stirred at 10°C to 20°C to form a uniform colloidal solution. Then, 1 mL to 5 mL of a 30% H2O2 solution was added dropwise to the colloidal solution as an oxidant. The solution was stirred for another 1 h to 2 h to form a light yellow FePO4·3H2O precipitate. S2, collecting the precipitate in S1 by centrifugation, repeatedly washing with deionized water, and drying the final product in a drying oven at 60°C to 80°C for 10h to 12h, placing the FePO4·3H2O precursor in a muffle furnace at 675°C to 825°C for calcination to obtain an iron source; S3, adding cerium sulfate and europium sulfate in a doping ratio of 1:1 to Li3PO4, stirring evenly, transferring the mixed solution into a reactor, reacting for 1h to 2h, and obtaining modified Li3PO4; S4, take the iron source obtained from S2 and the modified Li3PO4 obtained from S3 in a mass ratio of 1:1.5, dissolve them in deionized water, stir them evenly, then add the cationic surfactant octadecyl dimethyl benzyl ammonium chloride, the addition amount of octadecyl dimethyl benzyl ammonium chloride is 2.5% to 3.5% of the mass of the iron source, then put them into a reactor for hydrothermal reaction, pH is 1.45, reaction temperature is 100℃ to 120℃, reaction time is 4h to 6h, collect the solid powder in the reactor, filter it and vacuum dry it at 50℃ to 80℃ for 2h to 3h; S5. Place the dried solid powder in S4 in a tube furnace, calcine at 525°C to 625°C for 10h to 16h under the protection of argon, and cool to room temperature to obtain LiFePO4 product.
2. The lithium iron phosphate nanosphere according to claim 1, characterized in that: What is used in the said step S1 is 0.02 mol of (NH4)2Fe(SO4)2·6H2O and NH4H2PO4.
3. The lithium iron phosphate nanosphere according to claim 1 or 2, characterized in that: In step S2, the product is dried in a drying oven at 80° C. for 12 h.
4. The lithium iron phosphate nanosphere according to claim 1 or 3, characterized in that: In step S3, the mixed solution is transferred into a reactor to react for 1.5 hours.
5. The lithium iron phosphate nanosphere according to claim 1 or 4, characterized in that: The amount of octadecyldimethylbenzyl ammonium chloride added in step S4 is 3.0% of the mass of the iron source.
6. The lithium iron phosphate nanosphere according to claim 1 or 5, characterized in that: In the step S5, calcination is performed in a tube furnace at 625° C. for 16 hours.
Citation Information
Patent Citations
Carbon-free nanoscale lithium iron phosphate and preparation method thereof
CN101628714A
Preparation method of high-rate lithium iron phosphate microsphere
CN111186827A
Composite-coated lithium iron phosphate and preparation method therefor, and lithium ion battery
US20180097228A1
Lithium iron phosphate material and preparation thereof
WO2014056143A1
Cited By
Anti-rust and anti-corrosion modified coating film powder as well as preparation method and application thereof
CN121873595A